Implementation of the Problem-Based Learning Model to Enhance Students' Critical Thinking Skills in Information and Communication Technology Subjects - Yunulius, Yunulius (PT. Mifandi Mandiri Digital, 2025)
This study investigates the implementation of the Problem-Based Learning (PBL) model to enhance students’ critical thinking skills. The research aims to improve the critical thinking ability of students through the application of PBL in a classroom setting. A classroom action research design was employed, involving students of Grade X at SMA YAPIM Medan as the research subjects. The intervention was carried out over two cycles. Data collection techniques included observation, interviews, documentation of test results, and evaluations conducted at the end of each cycle. The findings of the study indicate that: (1) there is a significant effect of the PBL model compared to the discussion model on students’ problem-solving abilities; (2) students with high achievement motivation demonstrate significantly better critical thinking skills than those with low motivation; and (3) there is a significant interaction between the learning model, achievement motivation, and students' problem-solving abilities. It can be concluded that students taught using the PBL model exhibit superior problem-solving capabilities compared to those taught through traditional discussion methods.